Adesão à terapia antirretroviral em crianças e adolescentes infectados verticalmente pelo HIV: estudo prospectivo de longo prazo, COORTE UFMG, 2004-2014 - Laura Vieira de Lima Costa (2015)
With therapeutic advances, the HIV has become a chronic disease and with it the needs of patients and families. However, the success of the treatment depends on levels of adherence to the antiretroviral therapy of at least 95%. Objective: To evaluate adherence rate, and its determinants in a cohort of children and adolescents perinatally HIV-infected in two distinct moments, 2004 and 2014. Methods: Three questionnaires were used: a) hospital scale of anxiety and depression; b) the abbreviated instrument of quality life WHOQOLbref c) adherence questionnaire, adapted from the PENTA group. Adherence was assessed based on the number of antiretroviral therapy doses missed in the previous 3 days. Good adherence was defined as not having missed a dose in this period. Additional information were obtained in the cohort registration dataset, from patient medical records, and pharmacy records (ARVs dispensation). Statistical analyses were performed with SPSS software, using univariate analysis, followed by a multivariate logistic regression. Results: 64 subjects were enrroled: 50% were male; median ages were 4 and 15 years in 2004 and 2014, respectively. The adherence rates were similar in both moments (84.4% and 71.9%, respectively; p = 0.152). In 2004, good adherence was associated with higher scores of quality of life (p = 0.010). In 2014, in the multivariate analysis, to live with biological family, number of reasons for not taking the medication no greater than one and the mother being the person in charge for administering the medications were associated with good adherence, while having symptoms of depression was associated with poor adherence. Among the stated reasons for missing doses, were associated with poor adherence in both periods, 2004 and 2014,: "The person in charge was busy with other things to do", (p = 0.051 and p = 0.021); and "Having a different routine" (p = 0.021 and p = 0.015).The forgetfulness was the reason most often reported by participants for non-adherence in both periods (42.2% and 62.5%, respectively). Conclusion: Even with similar levels of adherence in both moments, an analysis of the number of previous antiretroviral schemes, the reasons for the last change of antiretroviral therapy and the progression in the clinical classification of the CDC, it can be inferred that these participants failed at some point, which is expected in a complex and chronic disease such as HIV, but that should be avoided. Pharmacy records for ARVS dispensation were consistent with self-report adherence rates. New studies aiming to increase adherence in the medium and long term, considering the late effects of antiretroviral therapy among patients followed up at referral service, are necessary.